Preparation and electrochemical properties of nitrogen‐doped carbon electrode material. Issue 1 (7th June 2021) - Zhang, Dandan; Nasreen, Saima
Abstract: In order to improve the lithium storage capacity of lithium‐ion battery anode materials, three nitrogen‐doped and nitrogen‐doped hollow carbon materials (Cw‐GO), nitrogen‐doped carbon aerogels, and three‐dimensional nitrogen‐doped porous carbon materials (PCMs) were prepared, and their electrochemical properties were studied. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and nitrogen adsorption desorption instrument were used to detect the morphology and structure of the samples. The electrochemical properties of the samples were tested by cyclic voltammetry (CV), impedance spectroscopy (EIS), and cyclic charge discharge (GCD). The results show that the introduction of graphene oxide (GO) can improve the specific capacitance and electrochemical activity of the composites; nitrogen‐doped carbon aerogel electrode material has better capacitance characteristics. PCM has a large specific surface area and a large capacitance response, which reaches 168.5 F g −1 at the current density of 1 A g −1 . When the current density is 10 A g −1, 1000 cycles of constant current charge and discharge test is carried out. When the current density is 20 A g −1, the specific capacitance of PCM keeps 88.3% of the original capacitance and has good electrochemical performance.